Anxiety and Depression of Nurses in a North West Province in China During the Period of Novel Coronavirus Pneumonia Outbreak. Issue 5 (19th August 2020) - Han, Lin; Wong, Frances Kam Yuet; She, Dong Li M; Li, Si Yan; Yang, Yun Fang; Jiang, Meng Yao; Ruan, Yue; Su, Qian; Ma, Yuxia; Chung, Loretta Yuet Foon
Abstract: Purpose: To investigate the anxiety and depression levels of frontline clinical nurses working in 14 hospitals in Gansu Province, China, during this period. Design: A cross‐sectional survey was conducted online between February 7 and 10, 2020, with a convenience sample of 22, 034 nurses working in 14 prefecture and city hospitals in Gansu Province, located in northwest China. Methods: A self‐reported questionnaire with four parts (demographic characteristics, general questions related to novel coronavirus‐infected pneumonia, self‐rating anxiety scale, and self‐rating depression scale) was administered. Descriptive statistics including frequencies, means, and SD s were computed. The associations between anxiety and depression with sociodemographic characteristics, work‐related concerns, and impacts were analyzed, followed by multiple stepwise linear regression to identify factors that best predicted the nurses' anxiety and depression levels. Findings: A total of 21, 199 questionnaires were checked to be valid, with an effective recovery rate of 96.21%. The mean ± SD age of the respondents was 31.89 ± 7.084 years, and the mean ± SD length of service was 9.40 ± 7.638 years. The majority of the respondents were female (98.6%) and married (73.1%). Some demographic characteristics, related concerns, and impacts of COVID‐19 were found to be significantly associated with both anxiety ( p < .001) and depression ( p < .001). Nurses who needed to take care of children or elderly relatives, took leave from work because they were worried about COVID‐19, avoided contact with family and friends, and wanted to obtain more COVID‐19‐related knowledge had higher levels of both anxiety and depression. Conclusions: Results show that nurses faced with the COVID‐19 outbreak are at risk for experiencing anxiety and depression. Demographic background, psychosocial factors, and work‐related factors predicted the psychological responses. The family responsibilities and burdens of women may explain the higher levels of anxiety and depression among nurses with these obligations as compared to those without. On the other hand, nurses who chose not to take leave from work or who did not avoid going to work during this period were less anxious and depressed. Clinical Relevance: Professional commitment might be a protective factor for adverse psychological responses. It is pertinent to provide emotional support for nurses and recognize their professional commitment in providing service to people in need.